Reaksi Pasar Modal Indonesia terhadap Pengumuman Pemindahan Ibu Kota Nusantara pada Saham yang Terdaftar di Bursa Efek Indonesia - Susilawaty, Lilis; Renaldi, Vikky; Effieta, Yolanda (SAFE-Network, 2024)
This research aims to analyze differences in abnormal returns throughout the observation period as well as differences in trading volume activity before and after the announcement of the relocation of the Indonesian capital city in 2019. Observations were carried out using a total sample of 46 companies in the infrastructure sector listed on the Indonesian stock exchange in 2019. This research was tested using two methods, namely to test the first hypothesis using a one-sample t-test for samples that were normally distributed and, for samples that were not normally distributed, using a non-parametric test, namely the one-sample Wilcoxon signed rank test. Meanwhile, the second hypothesis uses a paired samples T-test specifically for normally distributed data, while for those that are not normally distributed, the paired samples Wilcoxon signed ranked test will be used. The research results concluded that there were no abnormal returns or differences in trading volume activity throughout the observation period.